2019
DOI: 10.3390/ijerph16101814
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Education as Barriers and Facilitators to Nicotine Replacement Therapy Use for Smoking Cessation in Pregnancy: A Qualitative Study with Health Care Professionals

Abstract: Smoking during pregnancy is a leading cause of negative pregnancy and perinatal outcomes. While UK guidelines recommend nicotine replacement therapy (NRT) for smoking cessation during pregnancy, adherence to NRT is generally low and may partially explain why NRT appears less effective in pregnancy compared to non-pregnant smokers. This study aimed to identify and describe factors associated with NRT adherence from a health professional’s perspective. Two focus groups and one expert group were conducted with 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…This attitude was particularly true for women who planned to breastfeed. Prior literature is consistent with these findings, showing that postpartum individuals are unlikely to use pharmacological treatments for tobacco dependence [31,42,43]. The Health Belief Model may partially explain this.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This attitude was particularly true for women who planned to breastfeed. Prior literature is consistent with these findings, showing that postpartum individuals are unlikely to use pharmacological treatments for tobacco dependence [31,42,43]. The Health Belief Model may partially explain this.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, healthcare providers appear to be a trusted information source for communicating risk of relapse as well as the risks and benefits of pharmacological and behavioral interventions. Similar research has also shown healthcare clinicians as trusted resources for relapse prevention [41,42]. Educating pregnant individuals on their high risk of relapse may increase interest in postpartum relapse prevention treatments.…”
Section: Discussionmentioning
confidence: 84%
“…The NCSCT also provide practitioners' skills-based training modules in delivering stop smoking support. The similarity between LA and NHS Trusts' support methods and the utilisation of the same skills-based training packages illustrate the value of having a national centre to set standards of training and define treatments, all of which promote better clinical practice and better cessation outcomes for smokers [25] as well ensure the consistent factual messaging from health care professionals, valued by pregnant women [26].…”
Section: Discussionmentioning
confidence: 99%
“…It was felt that suggesting to women, who may be finding it difficult to quit, that they may be better trying a harm reduction approach would undermine practitioners’ current training and personal beliefs. It may also contribute to pregnant women’s confusion around NRT at a time when clear and consistent messages from health care professionals is needed [50] and increase the likelihood of women choosing and acting on information that allows them to continue to smoke when they may otherwise have successfully quit.…”
Section: Discussionmentioning
confidence: 99%